2020
DOI: 10.4018/978-1-5225-9787-2.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Alcohol Consumption Determinants in Turkey With Multinomial Probit Model

Abstract: The main objective of this study is to determine key factors that may have a significant effect on alcohol consumption in Turkey. For this purpose, the cross-sectional data obtained from the Turkish Health Survey conducted in 2010 and 2012 by the Turkish Statistical Institute were analyzed through the multinomial probit model. Results revealed that several key variables were found to be a significant determinant of alcohol consumption, such as gender, age, education, marital status, income, general health stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Whether there was multicollinearity between independent variables in the model was also tested. It was considered that those with a variance inflation factor (VIF) value of five and above led to a moderate multicollinearity and those with a value of 10 and above led to a high multicollinearity [ 68 ]. According to the VIF results presented in Tables 3 and 4 , there was no variable that led to multicollinearity problem between the variables.…”
Section: Resultsmentioning
confidence: 99%
“…Whether there was multicollinearity between independent variables in the model was also tested. It was considered that those with a variance inflation factor (VIF) value of five and above led to a moderate multicollinearity and those with a value of 10 and above led to a high multicollinearity [ 68 ]. According to the VIF results presented in Tables 3 and 4 , there was no variable that led to multicollinearity problem between the variables.…”
Section: Resultsmentioning
confidence: 99%
“…Although alcohol use and dependence predominate in men, gender has not consistently predicted relapse in alcohol use disorder studies. 21 , 22 While some studies found that female gender was significantly associated with better prognosis, more studies have not found a statistically significant relationship between gender and recurrence rates. 13 Women in AUD were found to be more likely than men to relapse following a stressful event or a drug-related cue, although the impact on relapse rates is unclear.…”
Section: Clinical and Research Consequencesmentioning
confidence: 99%